MiR-15a Participated in the Pathogenesis of Pterygium via Targeting BCL-2: An Experimental Research. (2nd January 2022) - Shen, Jianqin; Li, Huiyan; Chen, Yanhong; Jiang, Bo; Zhu, Miaomiao; Feng, Shi; Cui, Hongguang
ABSTRACT: Purpose: To compare the expression levels of miR-15a between pterygium and normal conjunctiva, and further investigate the potential role of miR-15a in the progression of pterygium. Methods: 21 cases of primary pterygium were enrolled in our study. The length of the pterygium invaded into the cornea and the total thickness of the pterygium were measured with anterior segment optical coherence tomography (AS-OCT). The pterygial and adjacent normal conjunctival samples of the 21 patients were collected. Expressions of miR-15a, BCL-2, Bax in both pterygium and normal conjunctiva were measured, and correlations between miR-15a and BCL-2, miR-15a and Bax, miR-15a and clinical parameters were made. Pterygium epithelial cells (PECs) were isolated, cultured and transfected with miR-15a mimic or miR-15a inhibitor to interfere the miR-15a expression levels. The regulation of BCL-2 expression by miR-15a was examined with Real-Time PCR (RT-PCR), Western blot and immunofluorescence. The regulation of Bax expression by miR-15a was also examined with Real-Time PCR (RT-PCR) and Western blot. The cell viability of the transfected PECs was measured with the CCK-8 assay and the apoptosis in these cells was detected using the TUNEL assay. Results: The expression of miR-15a, Bax were significantly decreased while the BCL-2 was significantly increased in pterygium ( p < .05). There was a negative correlation in expression between miR-15a and BCL-2 in pterygium tissues (r = −0.516, p < .05). We also found that relative miR-15a level was positively correlated with the length of pterygium invaded into the cornea (r = −0.570, p < .05). In cultured PECs, miR-15a could downregulate the expression of BCL-2 and upregulate the expression of Bax. Promotion of miR-15a could suppress cell proliferation and promote cell apoptosis in cultured PECs. Conclusions: Our study demonstrated that decreased expression of miR-15a in pterygium might be associated with the apoptosis and proliferation of abnormal cell via regulating BCL-2, which could subsequently contribute to the development of pterygium. Downregulation of miR-15a might also contribute to the pathogenesis of pterygium by other mechanisms including abnormal proliferation and neovascularization, which remain to be investigated.